PERANAN BADAN NARKOTIKA NASIONAL KOTA PAYAKUMBUH DALAM PELAKSANAAN REHABILITASI TERHADAP PECANDU NARKOTIKA - Failin Failin; Anny Yuserlina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Drug abuse is a complex issue that encompasses health, mental health, and legal aspects. It is an act that not only physically damages an individual but also robs them of their future and social awareness. Rehabilitation is one way to save addicts from dependence. The implementation of rehabilitation is based on Article 54 of Law No. 35 of 2009 concerning Narcotics and is supported by Government Regulation No. 25 of 2011 concerning the Protection of Drug Users from Illegal Drugs (IPWL). Keywods: The Role of the National Narcotics Agency, Rehabilitation, Narcotics Addicts.